Improving Interagency Collaboration, Innovation and Learning in Criminal Justice Systems Supporting Offender Rehabilitation - Hean, Sarah; Johnsen, Berit; Kajamaa, Anu; Kloetzer, Laure (Springer International Publishing : Imprint: Palgrave Macmillan, 2021)
This Open Access edited collection seeks to improve collaboration between criminal justice and welfare services in order to help prepare offenders for life after serving a prison sentence. It examines the potential tensions between criminal justice agencies and other organisations which are involved in the rehabilitation and reintegration of offenders, most notably those engaged in mental health care or third sector organisations. It then suggests a variety of different methods and approaches to help to overcome such tensions and promote inter-agency collaboration and co-working, drawing on emerging research and models, with a focus on the practice in European and Scandinavian countries. For academics and practitioners working in prisons and the penal system, this collection will be invaluable. .